Development of guided discovery learning model worksheet on sequences and series in vocational schools - Fimatesa Windari; Armiati Armiati; Yulkifli Yulkifli (International Conferences on Educational, Social Sciences and Technology)
Students’ worksheet is one of learning media to help students in studying mathematics. The worksheet is based on guided discovery learning. It is aimed to get the students accostumed in inventing mathematics concept, therefore the worksheet can make it easier for the students to understand sequences and series material. Sequences and series is one of the essential materials tought in vocational school since it is often correlated to problem solving. In general, the students in vocational school lack of ability to do problem solving. This research used Plomp educational design research that consist of initial preliminary research, development or prototyping stage and assesment phase. The instrument used in this research was validation sheet of students’ worksheet. The aim of this research was to produce valid, practice and effective worksheet. The result of this research showed that the Guided Discovery Model worksheet on Sequences and Series was valid, practical and effective.